(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Given that achieving gender equality is a global development agenda, girl’s participation in education has been taken as one of the most important indicators. The purpose of this article is to analyze the status of girls’ participation in higher education and explore the reasons behind the disparities among them. Similarly, some ways forward to address disparities of the girls’ participation are also explored. To analyze the status, the secondary data have been collected from University Grants Commission Nepal (UGC-Nepal). The data are tabulated, analyzed, compared, interpreted and the conclusion is drawn. Similarly, other related documents are consulted and reviewed to make recommendations for achieving gender equality in education. Girls’ participation in higher education has increased significantly from nineteen percent to forty-two percent during the thirty years. Though there exist many disparities in different groups, interventions need to start from the school education and access of technical higher education should be expanded in rural areas and to underprivileged groups. लैङ्गिक समानता हासिल गर्ने विश्वव्यापी विकास लक्ष्य प्राप्तीका लागि शिक्षामा छात्राहरूको सहभागितालाई मुख्य सूचकको रुपमा लिनेगरिएको छ । यो लेखमा खासगरी नेपालको उच्च शिक्षामा छात्राहरूको सहभागिताको अवस्था विश्लेषण गरी यसमा रहेका असमानताहरूकोखोजी गरिएको छ । यसका साथै उच्च शिक्षामा छात्रा सहभागितामा देखिएको असमानता कम गर्नका लागि अबलम्बन गर्न सकिने केही उपायहरुपनि प्रस्तुत गरिएको छ । विश्वविद्यालय अनुदान आयोगबाट प्रकाशित तथ्याङ्कीय प्रतिवेदनलाई तथ्याङ्कको स्रोतको रुपमा आधार लिएरछात्रा सहभागिताको अवस्था सम्बन्धी अध्ययन गरिएकोछ। आयोगले प्रकाशन गरेको तथ्याङ्कहरूलाई तालिकीकरण, विभिन्न वर्षका बीचतुलना, विश्लेषण र व्याख्या गरिएको छ । यसैगरी विषयसँग सम्बन्धित अन्य विभिन्न सामग्रीहरूको सहायताले उच्च शिक्षामा लैङ्गिक समानताहासिल गर्ने उपायहरू खोजी गरिएको छ । विगतको तीस वर्षमा उच्च शिक्षामा छात्रा सहभागिता उन्नाइस प्रतिशतबाट बढेर बयालिस पुगेको छ ।यद्यपी विभिन्न समूहहरूका बीचमा थुप्रै असमानताहरू विद्यमान छन । छात्राहरूको भर्नादर साधारण विषयहरूमा बढी छ । यस्तो असमानता कमगर्दै प्राविधिक उच्च शिक्षामा समेत छात्रा सहभागिता वृद्धि गर्न विद्यालय शिक्षादेखि नै छात्र र छात्राको समान सहभागिता र सिकाइमा ध्यानदिनुपर्छ । साथै ग्रामीण क्षेत्रमा समेत पहुँचको विस्तार गर्नु आवश्यक देखिन्छ ।